Mechanical and functional characteristics of hand grip strength in young female handball players - Dopsaj, M.; Valdevit, Z.; Bojic, I.; Copic, N. (Facta Universitatis: Series Physical Education and Sport, 2020)
The aim of this research was to define differences in functional and mechanical characteristics of isometric hand grip (HG) strength between young female handball players and the CG comprised of physically active girls with no experience in sport. 70 individuals participated in the research, 36 of whom were the best young female handball players (of cadet and junior categories) while 34 girls comprised the CG. The results obtained show that the young female handball players who took part in the tests achieved Fmax at the levels from 306.4±40.8 to 335.5±47.0 N and RFDmax at the levels ranging from 1918.1±366.8 to 2174.4±382.1 N/s for the non-dominant and dominant hand. When these results are compared to the ones achieved by the CG it is clear that the young female handball players had a statistically significant higher level of the maximum HG force of both arms as well as the higher level of maximum explosiveness. There was no statistically significant difference between the groups regarding all the indexes of dimorphism (ID) as well as the values of the time needed for achieving the maximum intensity of muscle excitation (tRFDmax). Therefore, it can be concluded that the handball players who underwent the testing procedures showed positive adaptation from the aspect of the mechanical characteristics of hand grip strength, which can most likely be ascribed to the phenomenon of biological adaptation to the training stimuli characteristic for handball. However, the same influence was not detected from the aspect of functional characteristics, more precisely, dimorphism.